Evaluasi dan Perbaikan Rancangan Antarmuka Pengguna Situs Web Dinas Koperasi dan Usaha Mikro Kota Malang dengan Menggunakan Metode Human-Centered Design (HCD) - Cerin Genias; Ismiarta Aknuranda; Hanifah Muslimah Az-Zahra (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Department of Cooperatives and Micro enterprises of Malang (Dinkop Malang) is a government agency engaged in cooperatives and micro businesses. The Dinkop Malang has a website that is used to spread information to the public, but the existing website needs to be improved to the problems such as sidebar that is too long, the content arrangement and use of the terms that are less appropriate, and writing style that is too small. Improvements are adapting the Human Centered Design (HCD) method, that is an iterative approach of system development with human consideration as the center of its activities so that the results obtained according to the needs of its user. The HCD stages are analysis the context of use, user requirements analysis, produce design solution, and evaluate the design solution. The results of the research is the improvement of the user interface design and comparison of usability achievements between the results of the initial evaluation and the final evaluation. In the results of the comparison on the aspects of effectiveness obtained 48% achievement in the initial evaluation to 100% at the final evaluation. On the efficiency aspect obtained average initial working time of 130.6 seconds to 36.91 second in final evaluation. The results of the comparison of user satisfaction aspects using the WEBUSE questionnaire obtained an enhancement in each WEBUSE category with the initial design value is moderate improved to good. The questionnaire selection is based on the reliability and satisfactory response from users. From the results of the comparison obtained, the improvement of the user interface design of Dinkop Malang website is able to answer the problems that exist in the initial design.